Comparative Analysis of the Public Health Role of Two Types of Death Investigation Systems in Texas: Application of Essential Services1. Issue 4 (17th March 2015) - Drake, Stacy A.; Cron, Stanley G.; Giardino, Angelo; Trevino, Vanessa; Nolte, Kurt B.
Abstract The purpose of this research was to assess the practices of death investigation agencies in Texas and to investigate the differences between justices of the peace (JPs) and medical examiner perceptions of their role and responsibilities. A survey was conducted in which justices of the peace and medical examiners (MEs) were questioned on their agency's policies and practices in regard to essential services provided using a recently published 50‐item instrument subdivided into 10 essential services areas. The study used a quantitative descriptive cross‐sectional design in which nonparametric analysis was used to ascertain differences between groups. The sample size for analysis was composed of 10 (83%) ME offices and 112 (15.5%) JPs. This statewide study found significant differences between MEs and JPs. These differences reflect the variation in educational background, understanding and implementation of essential services, and the appreciation of the needs of a system to be both collaborative and independent.